Simultaneous Escape Routing on Multiple Components for Dense PCBs - Chin, Ching-Yu; Chen, Hung-Ming (My University, 2013)
Simultaneous escape routing on dense boards is a very challenging task and lots of efforts have been spent. Most previous works focus on routing with one or two components, but in reality more components are possibly involved. In this paper, we propose a new simultaneous escape routing algorithm that considers multiple components at once. The proposed routing algorithm can solve simultaneous escape problem when two or more busses are connected to the same component. The experimental results show that, our routing algorithm can efficiently arrange escape paths properly to avoid net crossings and blockings between different busses.